MUATAN PENDIDIKAN RAMAH ANAK DALAM KONSEP SEKOLAH ALAM - Sayekti, Ika Candra; Sari, Novita Wulan; Sasarilia, Megan Nina; Primasti, Nabila Alfarina Mutiara (Profesi Pendidikan Dasar, 2018)
Abstract: The purpose of this research was to describe the implementation of friendly school children in Muhammadiyah Alam Surya Mentari Elementary School of Surakarta. The research methods used qualitative method because the data presented are words. If seen from the problems studied, this research is a descriptive research. Data was collected by interviewing, observing, and documentation. Validate data with triangulation of sources and methods. The data in this research are information from principals, teachers and students at Muhammadiyah Alam Surya Mentari Elementary School of Surakarta The results of the research describe that in the new student Admission there is no special selection, especially in terms of academic for students who register, this school also proved to receive children with special needs, while in the process of learning teacher always use a variety of learning methods with interesting media and teachers evaluate at the end of the chapters and end sub themes, midterm exam, final exam, and tasks. For student practice, students are helped by a worksheet prepared by the teacher. The results of this research explained that Muhammadiyah Alam Surya Mentari Elementary School of Surakarta has completed the indikator that must be owned by Child Friendly School.